Analyses of Monascus pigment secretion and cellular morphology in non‐ionic surfactant micelle aqueous solution. Issue 2 (14th December 2017) - Chen, Gong; Wang, Meihua; Tian, Xiaofei; Wu, Zhenqiang
Summary: Monascus pigments produced by Monascus spp . are widely used as natural food colourants. Extractive fermentation technology can facilitate the secretion of intracellular Monascus pigments into extracellular non‐ionic surfactant micelle aqueous solution, so as to avoid the feedback inhibition and decomposition. In this study, behaviour of the trans‐membrane secretion of Monascus pigments was investigated using morphological and spectroscopic analyses. Laser scanning confocal microscopy (LSCM) traced that pigment secretion occurred through rapid trans‐membrane permeation in 4 min, with a simultaneous conversion in pigment characteristics. Approximately 50% of intracellular pigments (AU470 ) extracted to extracellular broth with 40 g l −1 Triton X‐100, indicating the capacity for pigment extraction was limited by the saturation concentrations of surfactant. Scanning electron microscope (SEM) and transmission electron microscope (TEM) imaging showed some damage in the cell wall but an intact cell membrane with a slightly increased mycelial diameter. However, the physiological properties of the cell membrane, including integrity, fluorescence intensity and permeability, were altered. A diagram was provided to demonstrate the behaviour of Monascus pigment secretion induced by Triton X‐100. This study lays a foundation for the further investigation of Monascus pigment metabolism and secretion in extractive fermentation. Abstract : Nonionic surfactants can change the penetrability of cell membranes. The cell wall is damaged with a slightly increased mycelial diameter. Pigment characteristic changes during the pigment trans‐membrane process. Rapid trans‐membrane secretion of intracellular pigments to outside broth is revealed. The capacity for pigment extraction is limited by the saturation concentrations of surfactant.